Antifascism : the course of a crusade - Gottfried, Paul, 1941- (Ithaca [New York] : Northern Illinois University Press, an imprint of Cornell University Press, 2021)
"This book deals with the continuing appeal of antifascism as a political concept and as a tool for fighting a real or imagined fascist enemy. Antifascism has undergone significant changes in how it has understood and combatted a perceived fascist danger from the 1920s down to the present"--
Antifa and the Mainstreaming of Antifascism -- Origins of Antifascism -- Post-World War II Antifascism -- Defining and Redefining Fascism -- Populism vs. Antifascism -- The Uses and Abuses of "Conservative" Antifascism -- The Antifascist State -- Excursus : Antifascism and the Nature of Hobbesian Authority -- Afterthoughts.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 04, 2021).
JSTOR
Keywords: Fascism -- History; Anti-fascist movements -- History; Fascisme -- Histoire; Antifascisme -- Histoire; POLITICAL SCIENCE / Political Ideologies / Fascism & Totalitarianism; Anti-fascist movements; Fascism; Electronic books; History